Infection of burkholderia cepacia induces homeostatic responses in the host for their prolonged survival: the microarray perspective - Mariappan, V.; Vellasamy, K.M.; Thimma, J.; Hashim, Onn Haji; Vadivelu, J. (Public Library of Science, 2013)
Burkholderia cepacia is an opportunistic human pathogen associated with life-threatening pulmonary infections in immunocompromised individuals. Pathogenesis of B. cepacia infection involves adherence, colonisation, invasion, survival and persistence in the host. In addition, B. cepacia are also known to secrete factors, which are associated with virulence in the pathogenesis of the infection. In this study, the host factor that may be the cause of the infection was elucidated in human epithelial cell line, A549, that was exposed to live B. cepacia (mid-log phase) and its secretory proteins (mid-log and early-stationary phases) using the Illumina Human Ref-8 microarray platform. The non-infection A549 cells were used as a control. Expression of the host genes that are related to apoptosis, inflammation and cell cycle as well as metabolic pathways were differentially regulated during the infection. Apoptosis of the host cells and secretion of pro-inflammatory cytokines were found to be inhibited by both live B. cepacia and its secretory proteins. In contrast, the host cell cycle and metabolic processes, particularly glycolysis/glycogenesis and fatty acid metabolism were transcriptionally up-regulated during the infection. Our microarray analysis provided preliminary insights into mechanisms of B. cepacia pathogenesis. The understanding of host response to an infection would provide novel therapeutic targets both for enhancing the host's defences and repressing detrimental responses induced by the invading pathogen.